CONTINUING TEACHER EDUCATION: HOSPITAL CLASS INTERFACE BETWEEN EDUCATION AND HEALTH - de Lima Pedrosa, Cristiane Rose; de Fátima Gomes da Silva, Maria (Seven Editora, 2025)
The hospital classroom is a classroom that seeks to provide continued schooling for students admitted to hospitals for treatment. Therefore, teacher training for this setting requires topics that meet specific needs. This paper presents an excerpt from a study conducted in a hospital classroom, which aimed to assess teacher training that aligns with school services within the hospital setting. The methodology used is a qualitative approach, conducted during the pandemic, which allowed for an understanding of issues that address particular and complex health education situations and require different approaches. Data collection was conducted through semi-structured interviews via the Zoom Meetings platform with teachers with experience in hospital classrooms. In the results achieved, the teachers highlighted themes that encompass the particularity of teaching work in the hospital, such as: the interface between health and education, illness, the relationship between theory and practice and the emotional strengthening of teachers with the aim of identifying themes relevant to teaching in the hospital environment that contribute to a permanent process of improving the knowledge necessary for the teacher’s activity in this area. DOI: https://doi.org/10.56238/sevened2025.030-057